Evaluation of the Achievement Development Program Unit Kegiatan Mahasiswa (UKM) Football In Sekolah Tinggi Olahraga and Kesehatan Bina Guna - Dipa Pangestu; Eka Abdurrahman; Dicky Martin Naibaho; Farhan Helmy Lubis (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, 2023)
The aim of this research is to evaluate the coaching program for the Football Student Activity Unit at the Bina Guna College of Sports and Health. The research method used is descriptive qualitative. The approach used in this research is the CIPP model approach. Data collection techniques through observation, interviews and documentation of administrators, coaches, athletes and parents of athletes. The research results conclude: 1) Context is concluded in the good category. 2) Input regarding aspects of human resource availability is concluded in the good category. For the aspect of availability of facilities and infrastructure as well as funding sources, it is concluded in the medium category. 3) The process regarding aspects of implementing the training program, athlete acceptance system and coordination was concluded in the good category, while aspects of the coach acceptance system and use of facilities and infrastructure were concluded in the medium category. 4) Products regarding aspects of achievement and welfare are concluded in the medium category. Meanwhile, the organizational aspect is concluded in the poor category.